A review on synthesis, photophysical properties, and applications of dendrimers with perylene core. (15th August 2020) - Golshan, Marzieh; Rostami-Tapeh-Esmail, Ehsan; Salami-Kalajahi, Mehdi; Roghani-Mamaqani, Hossein
Graphical abstract: Abstract: Dendrimers are a novel class of polymeric materials with branches ramified from a core. Their structure has a great influence on their physical and chemical properties. The unique properties of dendrimers including the similar size, the highest degree of branching, the solubility in water, and the presence of internal cavities make them attractive for pharmaceutical and biological applications. Recently, applications of dendrimers with perylene-3, 4, 9, 10-tetracarboxylic diimide (PTCDI) core in the fields of dye-sensitive solar cells (DSSC), sensors, and organic light-emitting diodes (OLED) have been considered. These dendrimers are usually prepared in two divergent and convergent methods. In divergent approach, dendrimers grow from the core of a multifunctional molecule. In the convergent method, dendrimer is made in a stepwise way from end groups to inside. When the dendrons are large enough, they are attached to the core of the multifunctional molecule. The use of PTCDI chromophore as the core in dendrimers enhances the photostability, thermal stability, and high fluorescent intensity of these supramolecular structures. PTCDI can be modified by dendrimers by using its two different positions consist of imide and bay positions. Both types of modifications induce different and individual properties on PTCDI.